(untitled) (Microbes and Health, 2013)
Salmonella spp. are the most frequently reported cause of food-borne illnesses worldwide that are closely associated with the consumption of contaminated poultry and egg products. This study was designed to isolate and identify Salmonella, and evaluate its prevalence in chickens of different lines and ages during summer and rainy seasons. Cloacal swab samples (n=200) of apparently healthy chickens were collected. Isolated Salmonella were characterized using cultural, biochemical and serological examinations. A total of 104 samples (52%) were found to be positive for Salmonella spp. The prevalence of Salmonella spp. was significantly higher (p<0.01) during summer (67.78%) as opposed to rainy season (39.09%). Prevalence of Salmonella was 71.11% in broiler, 38.89% in layer and 25% in indigenous chicken. Broilers showed significantly higher prevalence of Salmonella as compared to layer and indigenous chickens (p<0.01). Among the five age groups, the highest prevalence was observed in chickens of 18-week of age (65%) and the lowest was in chickens of 2-week age (16.67%). The data of this study showed higher prevalence of Salmonella in broilers and underscored the need for detail epidemiological investigations as well as strict hygienic practices in farm and live bird markets all over Bangladesh. DOI: http://dx.doi.org/10.3329/mh.v1i1.13711 Microbes and Health Vol.1(1) June 2012 pp.30-33